Research Progress in the Field of Microbial Mitigation of Drought Stress in Plants - Shaffique, Shifa; Khan, Muhamad Aaqil; Imran, Muhamad; Kang, Sang-Mo; Park, Yong-Sung; Wani, Shabir Hussain; Lee, In-Jung (Frontiers in Plant Science, 2022)
Plants must defend themselves against ecological stresses, including drought. Therefore, they adopt various strategies to cope with stress, e.g., seepage and drought tolerance mechanisms allow plant development under drought conditions. There is evidence that microbes play a role in plant drought tolerance. Here we present a review of the literature describing the initiation of drought tolerance mediated by plant inoculation with fungi, bacteria, viruses, and several bacterial elements as well as the plant transduction pathways identified via archetypal functional or morphological annotations and contemporary “omics” technologies. Overall, microbial association plays a potential role in mediating plant protection responses to drought, which is an important factor for agricultural manufacturing systems that are affected by fluctuating climate.